An Improved Control Strategy for Managing Reactive Power and Reducing Capacity of Interlinking Converters by Participating of Electric Vehicles in Hybrid AC/DC Microgrids - Abbas Safari; Hesam Rahbarimagham (IEEE Access)
Nowadays, interface converters based hybrid AC/DC microgrids have gained great interests in smart grids. The interface converters can perform tasks such as accurate power sharing, power quality enhancement, bidirectional power transmission, and so on by using advanced and accurate control strategies. In this work, a dc voltage droop based hierarchical control is introduced for bidirectional power transfer by an interface converter in a hybrid AC/DC microgrid. This proposed approach can exchange active power between AC or DC subgrids according to the requirement of each subgrid with slight DC voltage deviation around its nominal value. Moreover, a reactive power control algorithm is presented which can compensate the reactive power of the AC subgrid based on the interface converter’s maximum rated capacity. Also, the impact of the participation of electric vehicles in the DC subgrid on the improvement of reactive power management and the capacity reduction of the interface converter is investigated. Another droop control is considered in the voltage control loop of the bidirectional boost converter in the electric vehicle to determine the participation rate of the electric vehicle in reactive power management through the charging and discharging of its battery storage system. The simulation results in Simulink MATLAB software illustrate that the compensation of reactive power by the interface converter improves significantly by employing the proposed control method and the maximum participation of electric vehicles, leading to a decrease in the rated capacity of the interface converter.